Circulating levels of plasminogen activator inhibitor-1 are associated with metabolic syndrome rather than with menopause. (3rd October 2019) - Basurto, Lourdes; Díaz, Alma; Rodriguez, Ana; Robledo, Ariadna; Vega, Sara; Garcia-Vega, Jessica; Martínez-Murillo, Carlos
Abstract: The plasminogen activator inhibitor type 1 (PAI-1) is the major determinant of fibrinolytic activity. PAI-1 concentrations are elevated in obesity, type 2 diabetes and metabolic syndrome (MetS). On the other hand, during menopause, fibrinolytic activity decreases and, consequently, PAI-1 concentration increases; however, it is debated whether menopause is an independent determinant factor of PAI-1 levels. The objective of this study was to evaluate the effect of hormonal and metabolic status on the concentration of PAI-1 in pre-and post-menopausal women. A case-control study was conducted in ninety pre-and post-menopausal women aged 45 to 55 years, matched by body mass index (BMI). Anthropometric measurements and biochemical determinations were performed on all participants. The fibrinolytic activity was determined by measuring PAI-1 by ELISA. Of all the women, 30% presented MetS. Women with MetS had higher values of PAI-1 (36.0 ± 19.1 vs 19.3 ± 14.8 ng/mL, p < .001); in contrast, no differences were observed when compared by hormonal status (20.7 ± 18.10 vs 20.2 ± 17.0 ng/mL, NS). The results of this study suggest that in women, MetS plays a more important role in the deterioration of the fibrinolytic mechanisms rather than their hormonal status. Therefore, the identification of cardio-metabolic factors is relevant to reduce the presence of thrombosis in post-menopausal women.